Moving from patches to quilts: developing self-aware, reflective leaders through curriculum innovation based on a Patchwork Text approach. Issue 6 (2nd November 2017) - Moen, Charlotte; Brown, Jeremy
Abstract: A Patchwork Text is a creative approach to learning and assessment based on short pieces of reflective writing to promote deep, meaningful reflection. A five-year study was undertaken to explore whether this approach supports postgraduate students' personal and academic development and the factors that influenced student experience, within one UK university. Our adapted approach encompasses patches of reflection, a structured Reflective Journal, formative feedback, and action learning within a constructively aligned curriculum. Between 2010 and 2015, 100 students attended the MSc Leadership Development programme and 71% (n=71) completed a questionnaire at the end of the first module. The questionnaire contained mainly open questions. The overwhelming majority of responses (89%, n=63) reported their experience of action learning was extremely positive. Eighty-five percent (n=58) reported that the Patchwork Text approach supported their academic development. Seventy-five percent (n=52) agreed the approach was helpful in relation to their summative assessment which comprised a reflective integrated portfolio. Thematic framework analysis of the qualitative data suggests the Patchwork Text approach increased self-awareness and insight; deepened and promoted on-going reflection; and facilitated critical thinking, analysis, and synthesis thereby enabling completion of the summative assignment. Findings suggest the adapted Patchwork Text approach increased students' self-awareness as well as supporting them with both their summative assignment and the development of academic writing skills.